MENGURANGI PERILAKU BERKATA NEGATIF MELALUI PROSEDUR AVERSI PADA ANAK AUTIS X - Yanti Karmila; Fatmawati -; Mega Iswari (Universitas Negeri Padang, 2018)
This research is done due to a problem that was found by the researcher at SDN 19 Kapalo Koto.A fifth grade student used to have negative behavior (using wrong words). The research aims at proving whether the aversion procedure by providing positive behavior (using acceptable words) can reduce the student’s negative behavior or not.This study uses a Single Subject Research approach, with desian A –B- A and data analysis techniques using visual analysis chart.The research aims at proving whether the aversion procedure by providing positive behavior (using acceptable words) can reduce the student’s negative behavior or not at SD Negeri 19 Kapalo Koto.Kata Kunci :Autis ; Mengurangi ; PerilakuNegatif ; ProsedurAversi